Development of quantitative real-time polymerase chain reaction coupled with high-resolution melting (HRM- qPCR) analysis for the diagnosis of Trypanosoma evansi in Canis lupus familiaris - Muñoz Calderon, Arturo Alejandro (2019)
The Trypanosomiasis caused by Trypanosoma evansi affects a wide diversity of mammals being zoonotic potential in man, with a case reported in 2005 in India. This haemoflagellate protozoan can parasitize most domestic mammals, being horses, dogs, and cattle the most affected species. Diagnostic tools for this parasitic infection are scarce, even though this trypanosomiasis can be very lethal if the animals are not treated. This work reports the development of a multi-diagnosis assay based on qPCR coupled to HRM that differentiates infections with diverse species of trypanosomatids and Leishmanias with zoonotic potential in peripheral blood samples from canines. The molecular marker selected was the Internal Transcribed Spacer (ITS1) present in the ribosomal RNA locus. This marker is highly conserved and present size variability among trypanosomes species. The results using as a template gDNA of different trypanosomatid species showed specific amplification with distinctive patterns in Melting Curves for T. evansi, T. cruzi, T. brucei, T. rangeli and different species of Leishmanias. This was confirmed in agarose gels, resulting in single or multiple bands with a size range from 250 to 480 bp. Its clinical validation was carried out on 14 peripheral blood samples from domestic canines from northeastern Argentina. The results showed positivity for infection with T. evansi in 36 % of the samples. Additionally, through this standardized technique, in one sample it could be detected infection with Leishmania infantum with low parasitemia, confirmed by sequencing and subsequent alignment of the ITS1 region with reference sequences. Therefore, molecular diagnosis of animal trypanosomiasis by HRM-qPCR represents a viable tool for wide-scale epidemiological studies, which may be used to report the true prevalence of the infection and allow implementation strategies to control these zoonotic diseases in Argentina, as well as the rest of South America, Africa, and Asia.